Results of computer tomography of the oldest suspected flute from Divje babe I(Slovenia): contribution to the theory of making holes in bones - Turk, Ivan; Pflaum, Miran; Pekarovič, Dean (Arheološki vestnik, 2005)
The suspected flute from the Mousterian site Divje babe Iin Slovenia was analysed with the aid of multi-slice computedtomography (MSCT) and reinterpreted in the light of twohypotheses, one of which envisages an artificial origin of theholes and the other a natural one. It was found that there werefour holes on the diaphysis; that at least two were made priorto the damage to the proximal and distal ends of the diaphy-sis; and that carnivores could not have made all the holes, butone at most. The holes are very probably artificial, made bythe combined use of stone and simple bone tools found at theDivje babe I site. The majority, and probably all the damagemade by carnivores on the suspected flute, are of secondaryorigin. Conclusions about the origin of the holes cannot there-fore be reached only on the basis of the damage, and the hy-pothesis of an artificial origin cannot be rejected.